Product Management of Self Help Groups in Andhra Pradesh - A Study - Gopisetti, Rambabu; Venkateshwarlu, H. (Indian Journal of Marketing, 2008)
Self Help Group (SHG) is a mechanism to extend mutual help and support through sharing ideas, experiences, information, other services and resources. The groups may be viewed as a process or an institution for socio-economic transformation leading to empowerment of the rural poor. It is worth to note that access to financial services is a basic objective of SHGs and may be a dominating one. However, they are basically credit plus groups. Credit plus implies that apart from credit facility, other activities related to economic business and social development are also undertaken with equal emphasis.